Clinical effectiveness of continuous peritoneal lavage in moderately severe to severe acute pancreatitis - Namhun Jong; Songil Rim; Hyesong Kim (Wolters Kluwer Medknow Publications, 2019)
Purpose: This study aims to evaluate the clinical effectiveness of continuous peritoneal lavage in moderately severe to severe acute pancreatitis (AP). Materials and Methods: We studied 58 patients with moderately severe to severe AP who were admitted from January 2015 to April 2017. Among these patients, 31 patients were treated only conventional therapy (control group). Twenty-seven patients were received continuous peritoneal lavage with conventional therapy (study group). Laboratory parameters and severity scores were compared before and 7 days after therapy between two groups. Mortality rate, the incidence of local complications and length of hospital stay were also compared between two groups. Results: There were no adverse events (bowel perforation and bleeding) associated with abdominal paracentesis for peritoneal lavage. The level of all parameters (white blood cell [WBC], C reactive protein [CRP], serum amylase, lactate dehydrogenase [LDH], blood glucose, serum creatinine, base excess, and serum calcium) and all the severity scores (systemic inflammatory response syndrome [SIRS], Marshall) were significantly improved 7 days after treatment compared before therapy in two groups (P < 0.05). We also compared the level of all laboratory parameters and severity scores between two groups 7 days after therapy. The level of serum amylase, blood glucose, and serum calcium was similar between two groups 7 days after treatment. In the study group, the level of WBC, CRP, LDH, serum creatinine, base excess, and severity scores (SIRS, Marshall) was significantly improved compared with control group 7 days after therapy (P < 0.05). Mortality rate was significantly decreased in the study group compared with control group (7.4% vs. 16.1%, P < 0.01). The incidence of local complication had also a significant difference between two groups (22.2% vs. 35.5%, P < 0.05). The length of hospital stay was significantly reduced in the study group compared with control group (33.1 ± 28.0 vs. 48.9 ± 36.2 days, P < 0.01). Conclusion: Continuous peritoneal lavage can significantly reduce mortality, complications, and length of hospital stay in moderately severe to severe AP.